Adverse impact of chronic kidney disease on clinical outcomes following percutaneous coronary intervention. Issue 6 (16th December 2020) - Bloom, Jason E; Dinh, Diem T; Noaman, Samer; Martin, Catherine; Lim, Michael; Batchelor, Riley; Zheng, Wayne; Reid, Christopher; Brennan, Angela; Lefkovits, Jeffrey; Cox, Nicholas; Duffy, Stephen J; et al.
Abstract: Aims: We aimed to assess the impact of the severity of chronic kidney disease (CKD) with long‐term clinical outcomes in patients undergoing percutaneous coronary intervention (PCI). Methods: We analyzed data on consecutive patients undergoing PCI enrolled in the Victorian Cardiac Outcomes Registry (VCOR) from January 2014 to December 2018. Patients were stratified into tertiles of renal function; estimated glomerular filtration (eGFR) ≥60, 30–59 and < 30 ml/min/1.73 m 2 (including dialysis). The primary outcome was long‐term all‐cause mortality obtained from linkage with the Australian National Death Index (NDI). The secondary endpoint was a composite of 30 day major adverse cardiac and cerebrovascular events. Results: We identified a total of 51, 480 patients (eGFR ≥60, n = 40, 534; eGFR 30–59, n = 9, 521; eGFR <30, n = 1, 425). Compared with patients whose eGFR was ≥60, those with eGFR 30–59 and eGFR<30 were on average older (77 and 78 vs. 63 years) and had a greater burden of cardiovascular risk factors. Worsening CKD severity was independently associated with greater adjusted risk of long‐term NDI mortality: eGFR<30 hazard ratio 4.21 (CI 3.7–4.8) and eGFR 30–59; 1.8 (CI 1.7–2.0), when compared to eGFR ≥60, all p  < .001. Conclusion: In this large, multicentre PCI registry, severity of CKD was associated with increased risk of all‐cause mortality underscoring the high‐risk nature of this patient cohort.